Trusted systems : sixth International Conference, INTRUST 2014, Beijing, China, December 16-17, 2014, Revised selected papers /: sixth International Conference, INTRUST 2014, Beijing, China, December 16-17, 2014, Revised selected papers. (2015) - Unknown
No abstract available